THE EFFECT OF EDUCATION CERTIFICATION ON PROFESSIONALISM OF CHRISTIAN EDUCATION TEACHERS - Purnama Pasande; Elsye Evasolina Tulaka; Ezra Tari (Indonesian Journal of Basic Education, 2019)
One of the effort to improve teacher professionalism requires certification to improve the proficiency and quality of teachers in implementing the teaching and learning process. In essence, certification and teacher competency standards are to get good and professional teachers. Having competence to carry out the functions and objectives of the school in particular, as well as educational goals in general, according to the needs of society and the demands of the times. The type of this research is quantitative research with survey methods. Christian Education (PAK) teachers who already have certification will have a significant influence on the work professionalism of Christian Education (PAK) teachers in carrying out their duties and responsibilities as a religious educator